(untitled) (Kinesiology, 2022)
This study aimed to examine the effect of acute beta-alanine (β-alanine) supplementation on jump performance after a strenuous fatigue protocol. Twelve healthy young men (age 21.4±0.5 years, body height 180.2±5.8 cm, body mass 76.6±9.2 kg) volunteered to participate in this randomized, double-blind, placebo-controlled trial. The experimental group ingested 3.2 g of β-alanine (separated into two 1.6 g dosages) mixed with 23 g of glucose, whereas the placebo group ingested two dosages containing 23 g of glucose. Following the supplementation intake, participants completed a jump protocol involving countermovement jump (CMJ) and four consecutive countermovement jumps (CMJ-4). Subsequently, a 4x400 m running fatigue protocol was carried out to produce fatigue. After the fatigue protocol, the same jumping tests were repeated, CMJ and CMJ-4, to evaluate the loss in jump height. The Mann-Whitney U test was used to analyze differences between the groups, whereas Wilcoxon signed-rank test was conducted to analyze differences within the groups with statistical significance set at p<.05. After β-alanine supplementation, no significant decrease in jump height was found in the experimental group in none of the tests after the fatigue protocol. Conversely, a significant decrease was noticed in the placebo group in CMJ but not in the CMJ-4 test. In conclusion, an acute β-alanine supplementation could attenuate jump height loss after the fatigue protocol. Therefore, athletes and coaches should consider acute β-alanine supplementation to attenuate sports performance decrease after high-intensity exercises in which muscle acidosis is highly increased. Key words: beta-alanine, countermovement jump, acute supplementation, sports performance